STUDENTS’ ATTITUDES TOWARD LEARNING ENGLISH PRONUNCIATION IN PHONETICS AND PHONOLOGY COURSE AT POHUWATO UNIVERSITY - Moonti, Gusfin Maulidyawanti; Laonga, Monalysa (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Pronunciation plays a crucial role in effective English communication, particularly for students learning English as a foreign language. This study aims to investigate students’ attitudes toward learning English pronunciation in the Phonetics and Phonology course at Pohuwato University. The focus of the study is on students’ attitudes, which include cognitive, affective, and behavioral aspects in learning English pronunciation. This research employed a descriptive quantitative research design. The sample consisted of 30 students from the English Education Study Program who had completed the Phonetics and Phonology course. Data were collected through a questionnaire using a five-point Likert scale and analyzed using descriptive statistics in the form of mean scores. The results indicate that students generally have a positive attitude toward learning English pronunciation. The cognitive attitude aspect obtained the highest mean score, indicating that students have strong awareness and beliefs about the importance of correct pronunciation in English communication. The behavioral attitude aspect was also categorized as positive, showing that students are willing to practice and accept feedback in pronunciation learning. However, the affective attitude aspect revealed that some students still experience anxiety and lack confidence when practicing pronunciation. Although students demonstrate good understanding and learning behaviors toward English pronunciation, emotional factors remain a challenge. Therefore, it is recommended that lecturers create a supportive learning environment, increase pronunciation practice activities, and utilize learning technology to help reduce anxiety and improve students’ pronunciation skills. ABSTRAK Pengucapan merupakan salah satu aspek penting dalam pembelajaran bahasa Inggris karena berpengaruh langsung terhadap kejelasan dan keberhasilan komunikasi. Penelitian ini bertujuan untuk mengetahui sikap mahasiswa terhadap pembelajaran pengucapan Bahasa Inggris pada Mata Kuliah Phonetics and Phonology di Universitas Pohuwato. Fokus penelitian ini adalah sikap mahasiswa yang meliputi aspek kognitif, afektif, dan perilaku dalam pembelajaran pengucapan bahasa Inggris. Penelitian ini menggunakan desain penelitian deskriptif kuantitatif. Sampel penelitian terdiri dari 30 mahasiswa Program Studi Pendidikan Bahasa Inggris yang telah mengikuti mata kuliah Phonetics and Phonology. Data dikumpulkan melalui kuesioner dengan skala Likert lima tingkat dan dianalisis menggunakan statistik deskriptif berupa nilai mean. Hasil penelitian menunjukkan bahwa mahasiswa secara umum memiliki sikap positif terhadap pembelajaran pengucapan bahasa Inggris. Aspek sikap kognitif memperoleh nilai mean tertinggi, yang menunjukkan bahwa mahasiswa memiliki kesadaran dan keyakinan yang kuat akan pentingnya pengucapan yang benar dalam komunikasi Bahasa Inggris. Aspek sikap perilaku juga berada pada kategori positif, yang menunjukkan bahwa mahasiswa memiliki kemauan untuk berlatih dan menerima umpan balik dalam pembelajaran pengucapan. Namun, aspek sikap afektif menunjukkan bahwa sebagian mahasiswa masih mengalami kecemasan dan kurang percaya diri ketika mempraktikkan pengucapan. Meskipun mahasiswa memiliki pemahaman dan perilaku belajar yang baik terhadap pengucapan bahasa Inggris, faktor emosional masih menjadi tantangan. Oleh karena itu, dosen disarankan untuk menciptakan suasana pembelajaran yang mendukung, meningkatkan aktivitas praktik pengucapan, serta memanfaatkan teknologi pembelajaran untuk membantu mengurangi kecemasan dan meningkatkan kemampuan pengucapan mahasiswa.